Scent and fragrances the fascination of odors and their chemical perspectives - Ohloff, Günther (Springer, 1994)
The author also describes the methods employed in the chemical synthesis of fragrances and the chemical modification of flavour and fragrance materials of natural origin. The book is completed by a description of 25 interesting fragrances
Literaturangaben. - Dt. Ausg. u.d.T.: Ohloff, Günther: Riechstoffe und Geruchsinn
Keywords: Geur; Quimica; Smaakstoffen; Vluchtige oliën; Perfumes; Smell; Duftstoff; Geruchssinn